(3QSGdI aj JYQja eYfi GddGfgGjIs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3ai JYQja MGd GdebOeI GdJi ehVhYgG ZjQ ehLhO hCf GdEjLGH hGdSdH cja jchf ajgG s
(3BNQgG (B:s
(3hGdMLI eG PcQfGg hgj aGSOI hGdHQGgjf GdVQhQjI JhLH GeJfGY GdJHGgi ai LGfHi GdeGVi hGdeSJbHd adfNJe GdebGdI s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdMGOjI YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdadSaI hGdefWbs